The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1167/iovs.15-17169
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Safety of Intravitreal Propranolol and Its Efficacy in Attenuation of Choroidal Neovascularization

Abstract: Citation: Nourinia R, Rezaei Kanavi M, Kaharkaboudi A, et al. Ocular safety of intravitreal propranolol and its efficacy in attenuation of choroidal neovascularization. Invest Ophthalmol Vis Sci. 2015;56:8228-8235. DOI:10.1167/iovs.15-17169 PURPOSE. Determine the safe dose of intravitreal propranolol (IVP), and evaluate its inhibitory effect on laser-induced choroidal neovascularization (CNV). METHODS.To determine the IVP safe dose, 32 rabbits were divided into 4 groups. Three of these groups received IVP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…This dose was chosen because we have previously demonstrated that a single intravitreal dose of propranolol at 0.3 μg per eye (0.03 mg/mL) could inhibit CNV in mice and is nontoxic in rabbits. 25 In an initial pilot study, we performed a dose-escalation series by using 0.003 μg, 0.03 μg, and 0.3 μg ICI-118,551 per eye (not shown). We found that 0.03 μg per eye inhibited CNV formation.…”
Section: Resultsmentioning
confidence: 99%
“…This dose was chosen because we have previously demonstrated that a single intravitreal dose of propranolol at 0.3 μg per eye (0.03 mg/mL) could inhibit CNV in mice and is nontoxic in rabbits. 25 In an initial pilot study, we performed a dose-escalation series by using 0.003 μg, 0.03 μg, and 0.3 μg ICI-118,551 per eye (not shown). We found that 0.03 μg per eye inhibited CNV formation.…”
Section: Resultsmentioning
confidence: 99%
“…These results provide us with the basis to explore higher doses of propranolol—up to 3 mg/kg body weight/day, adjusting dose by body weight—and even consider the use of a more selective β-blocker that could be more effective. It may be interesting as well to explore the effect of intravitreal injection of propranolol in clinical trials, as the case report recently published21 and based on the previous work by Nourinia et al , to determine the safe dose of intravitreal propranolol 22. Using intravitreal administration, the drug would achieve more easily the retina.…”
Section: Discussionmentioning
confidence: 99%
“…We thus justifiably focused on expression of major antiangiogenic TSP-1 and especially PEDF 37 as both have been found to be upregulated by propranolol. 10,38 TSP-1 was negligibly expressed in J774 CM and did not change in response to propranolol treatment; whereas PEDF protein expression was found to be markedly increased in propranolol-incubated J774 macrophages on dotblot, Western blot, ELISA assay, and immunohistochemistry (Figs. 4A-D); these changes in MPs were independent of VEGF, which was hardly affected by propranolol (Fig.…”
Section: Propranolol Induces Expression Of the Antiangiogenic Factor mentioning
confidence: 96%
“…These findings indicate that actions of propranolol on MPs depend on antagonism of more than one or two b-adrenoceptors, in contrast to other cell types. [8][9][10] To elucidate the antiangiogenic properties of propranolol via MPs, we measured inflammatory factors from incubated macrophages J774 cells, which were found to exert the most robust CNV reduction after 24 hours treatment with propranolol (10 lM; compared with other macrophages). Because the effects of propranolol were associated with caspase 3 activation (cleaved caspase 3) on endothelial cells (Fig.…”
Section: Propranolol Restricts Inflammation and Angiogenesis Through mentioning
confidence: 99%
See 1 more Smart Citation